A Direct‐Push Freezing Core Barrel for Sampling Unconsolidated Subsurface Sediments and Adjacent Pore Fluids. Issue 1 (13th September 2018) - Trost, Jared J.; Christy, Thomas M.; Bekins, Barbara A.
Abstract : Core Ideas: A direct‐push freezing core barrel (DPFCB) was developed and field tested. The DPFCB is suitable for sampling in coarse, unconsolidated sediments. The DPFCB freezes a 10‐ to 15‐cm plug that retains fluid and sediment in core sleeves. The DPFCB is interchangeable with unsaturated zone sampling tool strings. Contaminants passing through the unsaturated zone can undergo changes in narrow reaction zones upon reaching saturated sediments. Understanding these reactions requires sampling of sediment together with adjacent water and microbes in a manner that preserves in situ redox conditions. Use of a basket‐type core catcher for saturated, noncohesive sediments results in redistribution or loss of fluids during sample retrieval. Previously developed sample‐freezing drive shoes for hollow‐stem auger drilling rigs lessened fluid redistribution and retained all material that entered the core barrel in noncohesive sediment cores by freezing the base of the core with liquid CO2 . This technology has not previously been compatible with direct‐push rigs that are commonly used for contaminated site assessments. Here, we describe a freezing core barrel designed for direct‐push rigs that is compatible with commercially available tool strings. The device can be used interchangeably with unsaturated‐zone direct‐push tool strings, enabling core collection for studies of contaminant transport and transformation spanning unsaturated to saturated profiles. In all 10 attempts during testing near Bemidji, MN, the device froze a 10‐ to 15‐cm (4–6‐in) plug that retained fluids and sediments in a 1.2‐m (4‐ft)‐long, 5.0‐cm (2.0‐in)‐diameter polyvinyl chloride (PVC) sleeve. Cores were collected from variably saturated sediments spanning the capillary fringe through the upper 2 m of the saturated zone in sandy glacial outwash sediments. The median recovery was 81% of the drive length, similar to a sample‐freezing drive shoe developed for a wire‐line piston core sampler operated with a hollow‐stem auger drill rig.